The Rehabilitation Role in Chronic Kidney and End Stage Renal Disease - Domenico Intiso (Karger Publishers, 2014)
Chronic kidney disease (CKD) worldwide is rising markedly becoming a priority public health problem. The progression of CKD cause functional limitation and severe disability with poor quality of life. The aim of present review was to highlight the effect of rehabilitation in CKD and ESRD subjects. The rehabilitative process is unique in treating disabled people according to a holistic approach with the aim of supporting a person's independent living and autonomy. CKD are associated with an increased risk of functional impairment, independent of age, gender, and co-morbidities. Clinicians should counsel patients with CKD including frail elder people to increase physical activity levels and target that regular physical activity including aerobic or endurance exercises training benefits health. In old subjects with CKD and multiple functional impairments, the traditional disease based model should be changed to individualized patient-centered approach that prioritizes patient preferences. Patients receiving haemodialysis have a considerably lower exercise tolerance, functional capacity, and more muscle wasting than healthy subjects or patients with less severe CKD. Exercise training or comprehensive multi-dimensional strategy and goal-oriented intervention should be also provided in ESRD older subjects. Structured prevention programs based on reducing the risk factors for CKD and rehabilitative strategies could reduce disability occurrence.